PENGARUH PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING BERBASIS LINGKUNGAN SEKOLAH TERHADAP KREATIVITAS DAN HASIL BELAJAR BIOLOGI PESERTA DIDIK KELAS XI SMA NEGERI 9 DENPASAR - I Made Subrata; A. A. Istri Mirah Dharmadewi; Herlina Lium (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to determine the effect of the school environment-based Contextual Teaching and Learning (CTL) learning model on the creativity and biology learning outcomes of class XI students of SMA Negeri 9 Denpasar in the 2024/2025 academic year. The CTL model emphasizes the connection between subject matter and real life, which in this study is based on the school environment. The population of this study was all 11th grade students of SMA Negeri 9, and two classes were sampled, each with 36 students. One class served as the experimental group and the other as the control group. The experimental group was given environment-based CTL learning, while the control group was given conventional learning with material presentation and questions and answers. Data were collected through learning outcome tests and creativity sheets. The research data were analyzed using t-test and MANOVA statistical analysis. Prior to the parametric statistical analysis, prerequisite tests were conducted in the form of normality, validity, and homogeneity tests. The results of the statistical analysis showed that the average learning creativity of the experimental class was 87.75 and learning outcomes were 84.94. Meanwhile, the control class obtained average scores of 78.36 and 72.97, respectively. The MANOVA test showed a significance value of 0.000 (<0.05) and Wilk's Lambda of 0.158, indicating that there was a simultaneous influence of the school-based Contextual Teaching and Learning (CTL) learning model on students' creativity and biology learning outcomes. These results prove that the school-based CTL model is effective in improving the quality of biology learning at SMA Negeri 9 Denpasar in the 2024/2025 academic year.